QR CODE Assisted Mathematics Pocket Book for Grade IV Elementary School. - Mustika, Ayu; Mulyono, Dodik; Satria, Tio Gusti (PrimaryEdu : Journal of Primary Education, 2022)
This study aims to determine the level of validity and practicality of the learning media " QR Code -assisted Pocket Book " in mathematics lessons on polygons for grade IV Elementary School 1 Megang Sakti. This research is development research using the ADDIE development model. Based on the results of the assessment analysis conducted by three experts, namely: linguist, media expert, and material expert. The validators stated that the QR Code -assisted Pocket Book "in the polygon material mathematics lesson for grade IV SD Negeri 1 Megang Sakti has met the valid criteria with an average score of 0.87 with the High criteria. As for the practicality of the QR Code -assisted pocket book in mathematics lessons, the polygon material for class IV of the State Elementary School 1 Megang Sakti meets the very practical criteria with an average score of 96%, so it can be concluded that the QR Code -assisted pocket book meets the valid, practical criteria. and can be used in learning.